THE EFFECTIVENESS OF PRECISION MAUNG NIGHT PATROLS AND CRIMINAL PUNISHMENT IN DEALING WITH TEENAGE BRAWLS IN CIREBON CITY - Fathurohman, Dadan Taufik; Rahman, Alfin; Wijaya, Ega Putri; Najiyullah, Nana; Azzahra, Yumna Shafa (Jurnal Abdisci, 2025)
Abstract Background. Teenage brawls are a social problem that still often occurs in Cirebon City, causing public unrest and potentially causing casualties. The Cirebon City Police has implemented a countermeasures strategy in the form of Maung Presisi night patrols and applying criminal sanctions for the perpetrators of brawls as a preventive and repressive effort. Aims. This study aims to analyze the effectiveness of Maung Presisi patrols in preventing juvenile brawls and evaluate the application of criminal punishment in providing a deterrent effect to perpetrators. Methods. The research method used is empirical juridical with a qualitative approach. Data is obtained through direct interviews with police officers at the Cirebon City Police, especially the Jatanras unit, as well as observations in the field. Result. The study's results show that Maung Presisi patrols have an important role in reducing the number of brawls, especially in vulnerable areas, although there are still obstacles such as limited personnel and coordination with the community. Meanwhile, the application of criminal penalties for juvenile brawlers, especially those who carry sharp weapons or cause injury to victims, has been shown to have a deterrent effect, but its effectiveness depends on the consistency of law enforcement and the support of rehabilitation programs. Conclusion. This study concludes that the combined approach of preventive patrols and strict legal sanctions needs to be improved by involving various parties, including schools and the community, to create a safer and more conducive environment for adolescents in Cirebon City. Implementation. The number of brawls in Cirebon City can be significantly reduced with the collaboration between the police, schools, parents, and the community. Prevention efforts based on education and coaching must go hand in hand with strict law enforcement so that the solutions implemented can have a long-term impact in creating a safer and more conducive environment for the younger generation.